(untitled) (Web of Teachers: Inderscience Research, 2024)
This article describes modern education, its content, the essence of organizing a modern approach to primary education, foreign experience in modern primary education. The content of modern primary education in the education of the USA, Singapore, Finland and Uzbekistan is comparatively analyzed.